2006
DOI: 10.1590/s1516-35982006000600017
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilidade, cecotrofia, desempenho e rendimento de carcaça de coelhos em crescimento alimentados com rações contendo óleo vegetal ou gordura animal

Abstract: RESUMO -Dois experimentos foram conduzidos com o objetivo de avaliar o efeito da inclusão de níveis crescentes (1,5; 3,0; 4,5 e 6,0%) de óleo de soja (OS) ou gordura animal (gordura de porco -GA) nas dietas sobre a digestibilidade aparente dos nutrientes e o desempenho de coelhos em crescimento. No ensaio de digestibilidade, foram utilizados 72 coelhos da raça NZB, distribuídos em um delineamento inteiramente casualizado, com nove tratamentos e oito repetições. A adição de diferentes níveis de OS ou GA às diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
0
1
0
8
Order By: Relevance
“…Although vegetable oils and animal fats have a different fatty acid composition, considering the isoenergetic diets in the present study, the inclusion of different lipid sources up to 2.5% resulted in no differences in performance of growing rabbits, confirming the results obtained by Falcão e Cunha et al 2000who evaluated the inclusion of up to 3.5% soybean oil and tallow in growing rabbit diets and found no significant effect on final weight, average daily gain, or feed conversion. Higher levels of dietary vegetable oils and animal fats were evaluated by Ferreira et al (2006), who observed no effect of the lipid source on the daily weight gain or feed conversion of rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Although vegetable oils and animal fats have a different fatty acid composition, considering the isoenergetic diets in the present study, the inclusion of different lipid sources up to 2.5% resulted in no differences in performance of growing rabbits, confirming the results obtained by Falcão e Cunha et al 2000who evaluated the inclusion of up to 3.5% soybean oil and tallow in growing rabbit diets and found no significant effect on final weight, average daily gain, or feed conversion. Higher levels of dietary vegetable oils and animal fats were evaluated by Ferreira et al (2006), who observed no effect of the lipid source on the daily weight gain or feed conversion of rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto nesse trabalho isso não foi observado, talvez como consequência da tentativa de manter os valores de energia das dietas próximas durante a formulação das mesmas. Ferreira et al (2006) e Pérez et al (1996) não observaram diferenças na CDMO, CDPB e na ingestão de MS, quando forneceram dietas com alto percentual lipídico para coelhos em crescimento.…”
Section: Methodsunclassified
“…Não foi observado efeito dos tratamentos sobre a CDEE; resultados diferentes deste foram encontrados por Ferreira et al (2006), Arruda et al (2000), Cheeke (1995), Lopes et al (1997), Xiccato (1996), Cesari et al (2010) que observaram uma melhor CDEE em dietas com maior percentual de lipídios. Por outro lado, Maertens et al (1985), Falcão et al (1996) observaram que quando a inclusão de lipídio é alta pode ocorrer diminuição da CDEE, provavelmente porque a eficiência digestiva e atividade da microflora no ceco são negativamente afetados pelo excesso de lipídios.…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Utilizaram-se como critérios de inclusão apenas artigos científicos na área de alimentação e nutrição de coelhos entre 2000 e 2010. (27) ; Arruda et al (28) ; Furlan et al (29) ; Furlan et al (30) ; Vieira et al (31) ; Faria et al (32) ; Furlan et al (33) ; Santos et al (34) ; Furlan et al (35) ; Lui et al (36) ; Lui et al (37) ; Ferreira et al (38) ; Furlan et al (39) ; Furlan et al (40) ; Michelan et al (41) ; Scapinello et al (42) ; Barbosa et al (43) ; Dávila et al (44) ; Ferreira et al (45) ; Faria et al (46) ; Haponik et al (47) ; Euler et al (48) .…”
Section: Methodsunclassified